The difference uses of panoramic photo and cbct evaluation of the gnathoplasty surgery outcome - Ayu Wahyuni; Muliaty Yunus; Muhammad Ruslin (DiscoverSys Inc., 2017)
Objective: Gnathoschisis is the most common congenital craniofacial abnormality in patients with cleft lip and/or palate (CL and/or P). The panoramic radiograph is one means to establish a diagnosis and treatment plan with two-dimension photograph. The cone-beam computed tomography (CBCT) is one means of supporting the maxillofacial to get a three-dimension photograph. The aim of this study was to determine the difference in the results of the use of panoramic photos and CBCT in evaluation before and after gnathoplasty surgery.Material and Methods: This is an observational descriptive research with cross-sectional study method. All samplesÂ that meet the suitable criteria are put in this research. The data gained by collecting status card at medical record installation about photo panoramic application in gnathoschisis patients was then compare to the examination with CBCT.Results: The result performed shows that there is a significant difference between panoramic and CBCT picture. The CBCT provide better evaluation about teeth age and segment position of jaw curve from the cleft size. While the panoramic photo provides a widely coveredÂ area to observe facial and teeth bone.Conclusion: The CBCT results are more accurate in evaluating gnathoplasty surgery than panoramic photo; however, exposure to the radiation should be considered.